Whose Authenticity? Exploring Host–Guest Interactions in Cultural Tourism Experiences in Indonesia - Azizi, Alif Firman (Advances in Tourism Studies, 2024)
This study investigates how cultural authenticity is constructed and negotiated through host–guest interactions in Indonesian tourism settings. While authenticity has long been a central concept in tourism research, much of the existing literature treats it as either an objective attribute of cultural products or a subjective perception held by tourists. This study instead emphasizes authenticity as a relational process that emerges in encounters between hosts and visitors. Using a qualitative design, data were collected through semi-structured interviews with local performers, artisans, and cultural guides, as well as in-depth conversations with domestic and international tourists in selected cultural destinations in Bali and Lombok. Participant observation of performances, festivals, and heritage sites complemented the interviews. Thematic analysis revealed three dominant patterns: first, hosts often engage in strategic performances that balance cultural pride with commercial expectations; second, tourists’ perceptions of authenticity vary, with some seeking immersion in local traditions while others prefer commodified representations; third, tensions arise when host communities feel pressured to alter or simplify traditions to meet visitor demand.